Think tank research quality : lessons for policymakers, the media, and the public - Welner, Kevin Grant; Hinchey, Patricia H.; Molnar, Alex; Weitzman, Don (Emerald Publishing Limited : Information Age Publishing, 2010)
Education policy over the past thirty years has been powerfully influenced by well-funded and slickly produced research reports produced by advocacy think tanks. The quality of think tank reports and the value of the policies they support have been sharply debated. To help policymakers, the media, and the public assess these quality issues, the Think Tank Review Project provides expert third party reviews. The Project has, since 2006, published 59 reviews of reports from 26 different institutions. This book brings together 21 of those reviews, focusing on examining the arguments and evidence used by think tanks to promote reforms such as vouchers, charter schools and alternative routes to teacher certification. The reviews are written using clear, non-academic language, with each review illustrating how readers can approach, understand and critique policy studies and reports. The book will be of interest to practitioners, policymakers, researchers, and anyone concerned with the current debates about educational reform.